Institute of Dedication to the State in the Study of Organizational Communication Patterns - Nuryanto, Guyub; Sariyati, Sariyati; Kuncoroyakti, Yohanes Arie; Fajar, Abdul Malik (Lentera Ilmu Nusantara, 2024)
Communication is the most important aspect to build organizational integrity because it can determine the effectiveness and smooth direction of communication that occurs in the organization. The title of this research is